Designing for Indoor Air Quality: Using Plants and Ecofriendly Materials - Anushka Singh Kaushik; Samreen Siraj Siddiqui (International Journal of Sustainability, 2025)
This study’s main objective is examining passive design techniques that optimize energy efficiency, such as natural ventilation, daylighting, and thermal insulation. It explores their potential to reduce energy consumption and enhance occupant comfort while minimizing reliance on mechanical systems. Sustainability is a key focus throughout the study, highlighting the importance of adopting sustainable practices in the design and construction industry. The research explores strategies for reducing environmental impact, minimizing waste, and optimizing resource efficiency within interior spaces. Furthermore, the research investigates the selection and use of eco-friendly materials as an integral aspect of sustainable interior design. It explores the benefits of utilizing recycled and low VOC (volatile organic compound) products, considering their environmental impact, indoor air quality improvement, and potential to promote occupant health. Green labelling programs are evaluated to understand their impact on sustainable interior design. The study assesses their certification criteria and their influence on material selection, energy performance, and indoor environmental quality. Maintaining a healthy indoor environment is another critical aspect investigated in the research. It examines strategies for ensuring good indoor air quality, adequate lighting, and acoustics within interior spaces. The study considers the impact of design decisions on occupant health and well-being, emphasizing the importance of incorporating biophilic design principles and creating spaces that promote mental and physical well-being. Finally, the study presents a glimpse into the future of sustainable design, discussing emerging trends, technologies, and innovative approaches that can further advance sustainable interior design practices. The study emphasizes the role of sustainable interior design in shaping a more sustainable future, where environmental responsibility and occupant well-being are at the forefront of design decisions.
Keywords: Sustainable interior design; eco-friendly; indoor environment; interior design; passive design